2015
DOI: 10.15415/jmrh.2015.12007
|View full text |Cite
|
Sign up to set email alerts
|

Study on Nutritional Problems in Preschool Aged Children of Kaski District of Nepal

Abstract: Undernutrition remains a key public health burden in Nepal. This study aimed to measure knowledge, attitudes, and beliefs about nutritious food amongst mothers of 3 – 5-year-olds from rural and urban areas. A cross-sectional mixed-methods approach comprised a quantitative survey and qualitative focus groups. The community-based survey included 524 mothers of children who are no longer breastfed. Open-ended and structured questions investigated knowledge, beliefs and attitudes about nutritious food, child feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In Ethiopia, it has been reported that the prevalence of stunting and wasting was 37% and 7%, respectively [ 3 ]. Undernutrition causes morbidity and mortality among children, and food insecurity is more prevalent [ 4 ]. Its high rates may also pose a significant obstacle to achieving better child health and nutritional outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, it has been reported that the prevalence of stunting and wasting was 37% and 7%, respectively [ 3 ]. Undernutrition causes morbidity and mortality among children, and food insecurity is more prevalent [ 4 ]. Its high rates may also pose a significant obstacle to achieving better child health and nutritional outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Household food insecurity (HFI) was measured using the Household Food Insecurity Access Scale (HFIA), which has nine questions and is related to the households’ experience of food insecurity in the 12 months preceding the survey ( 29 ) . Then, the HFIA prevalence indicators were categorised households into four ( 30 ) levels of HFI: food secure, mild, moderately and severely food insecure. For the present study, only two levels other Household Food Insecurity Access Scale (food secure and insecure) was used because the sample size for this study was small ( 31 ) .…”
Section: Methodsmentioning
confidence: 99%
“…The short- and long-term consequences of severe acute malnutrition are associated with morbidity and mortality [ 2 , 3 ]. High rates of severe acute malnutrition can also lead to poor child health and nutritional outcomes [ 4 ]. Globally, about 16.4 million children under five years of age were affected by severe acute malnutrition [ 5 , 6 ], and out of whom, 23% accessed ready-to-use therapeutic foods.…”
Section: Introductionmentioning
confidence: 99%